Institutional Trust 2001 - Insitutional Trust 2001 - Holmberg, Sören; Weibull, Lennart; MedieAkademin; TNS Gallup (University of Gothenburg, 2014)
Since 1997, MedieAkademin has carried out an annual survey titled The Institutional Trust. The survey has focused on major social institutions, such as the parliament, big business, the daily press, and TV/radio, as well as some specific companies such as Sveriges Television, TV4, IKEA, Skandia, and Volvo. The number of institutions included has varied somewhat over the years. Some of the institutions and companies have been measured every year while others have been investigated more irregularly.

The survey was carried out by NFO Infratest and involved 759 individuals who were interviewed by telephone between October 16 and November 5, 2001. The 2001 survey also included questions about how people perceive the Swedish democratic system, as well as their assessments of how politicians, the business world, the Swedish royal court, and the media function.

Purpose:

To study the trust that Swedish people have in social institutions, political parties, media, brands/companies, and leaders.

MedieAkademins förtroendebarometer har genomförts årligen sedan 1997. Undersökningen har varje år dels avsett ett urval viktiga samhällsinstitutioner som exempelvis riksdagen, storföretagen, dagspressen och radio-TV, dels ett antal konkreta medier, bl.a Sveriges Television och TV4, och specifika företag, som t ex IKEA, Skandia och Volvo. Antalet bedömda institutioner har varierat något mellan enskilda år. Vissa av institutionerna/medierna/företagen har mätts varje år, andra har studerats mer oregelbundet.

Undersökningen 2001 omfattade 759 intervjupersoner och genomfördes via telefon 16/10 - 5/11 2001 av NFO Infratest. I 2001 års undersökning ingick även frågor om människors föreställningar om svensk demokrati och om hur man bedömer att bland annat politiker, näringsliv, kungahus och medier fungerar.

Syfte:

Studera svenska folkets förtroende till samhällsinstitutioner, politiska partier, medier, varumärken/företag och ledare.
Förtroendebarometer 2001
Keywords: mass media; massmedia; trust; förtroende; political attitudes; politiska åsikter; trust in government; förtroende för regeringen; Media; Media; POLITICS; POLITIK; Social Sciences; Samhällsvetenskap